High mortality and coinfection in a prospective cohort of human immunodeficiency virus/acquired immune deficiency syndrome patients with histoplasmosis in Guatemala (2017)
Histoplasmosis is one of the most common and deadly opportunistic infections among persons living with human immunodeficiency virus (HIV)/acquired immune deficiency syndrome in Latin America, but due to limited diagnostic capacity in this region, few data on the burden and clinical characteristics of this disease exist. Between 2005 and 2009, we enrolled patients 18 years of age with suspected histoplasmosis at a hospital-based HIV clinic in Guatemala City. A case of suspected histoplasmosis was defined as a person presenting with at least three of five clinical or radiologic criteria. A confirmed case of histoplasmosis was defined as a person with a positive culture or urine antigen test for Histoplasma capsulatum. Demographic and clinical data were also collected and analyzed. Of 263 enrolled as suspected cases of histoplasmosis, 101 (38.4%) were confirmed cases. Median time to diagnosis was 15 days after presentation (interquartile range [IQR] = 5-23). Crude overall mortality was 43.6%; median survival time was 19 days (IQR = 4-69). Mycobacterial infection was diagnosed in 70 (26.6%) cases; 26 (25.7%) histoplasmosis cases were coinfected with mycobacteria. High mortality and short survival time after initial symptoms were observed in patients with histoplasmosis. Mycobacterial coinfection diagnoses were frequent, highlighting the importance of pursuing diagnoses for both diseases. and copy; 2017 by The American Society of Tropical Medicine and Hygiene.